Living with Substance Abused Spouse: A Phenomenological Approach - Saba Touseef, Rabia Iftikhar, Syed Messum Ali Kazmi, Ayesha Majeed (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Substance abuse is social problem throughout the world due to which not only the life of addicted person but also his families especially his spouses are also affected. Aim: The current study aimed to explore the lived experiences of the spouses of substance abused men and the impact of their husband addiction problem on different aspects of their lives. Material and Method: The design of this study was a cross sectional study design and this study was conducted at Mayo Hospital Lahore. A sample size of eight (N=8) were recruited. Interview guide consists of open ended questions which were developed for the purpose of data collection. Semi structured interview approach was employed for conducting interview. Interpretative phenomenological analysis was used to analyse the interviews. Results: Results from analysis yielded eleven super ordinate themes. These includes social support, challenges on societal level, unhealthy home environment, unhealthy relationship supportive wife, financial instability, physiological problems, psychological complaints, change in personality, concerned mother and religious coping. Conclusion: The results will contribute to understanding the impact of substance abuse of men on their spouses. It will help in developing an educational program for those people who are the risk by increasing their awareness and changing their behavior for preventing addiction problem and will also aid in developing counseling plans for the spouses of substance abusers. Keywords: Substance abuse, Interpretive Phenomenological Analysis, Financial Instability, Religious Coping